Postcard with French postal stamps commemorating the centenary of the birth of Marie Curie - Autier, Ph.; Pheulpin, Jean (1967)
Cachet shows the Curie laboratory in Paris, and stamps depict Marie Curie with a bowl of radium.
Keywords: Women in science; Curie, Marie, 1867-1934; Women physicists; Women in physics; France; Women scientists; Chemists; Postmarks; Commemorative postage stamps; Women chemists; Science on postage stamps; Nobel Prize winners; Women in chemistry; Cachets (Philately); Physicists; Postage stamps; Postcards; Women physical scientists; Women Nobel Prize winners